Flipped Learning Theory, Policies, and Practices - Kurban, Caroline Fell; Şahin, Muhammed (Emerald Group Publishing Ltd., 2016)
…
Caroline Fell Kurban (MEF Author)
Muhammed Şahin
Keywords: Educational research; Education; Flipped learning